Creative interventions for symptoms of postnatal depression: A process evaluation of implementation. Issue 1 (2nd January 2019) - Fancourt, D.; Perkins, R.
Abstract: Background : This article is a process evaluation of a three-arm randomised controlled trial (RCT) comparing the effects of creative interventions on symptoms of postnatal depression (PND) in new mothers. Methods : Analyses of quantitative evaluation data from 91 participants and qualitative interviews and focus groups with 80 participants and 3 members of staff. Results : Key assumptions of the RCT, including how the delivery of the intervention was achieved and what the intervention involved, are explored. Data suggest that the intervention was delivered as planned with a high level of fidelity. Key uncertainties surrounding the project, in particular unanticipated challenges that had to be overcome during the RCT, are also discussed and simple recommendations for improvement are made. Conclusion : This process evaluation aims to illuminate the outcome and mechanisms data from the RCT and enable organisations or individuals to ascertain the feasibility of establishing their own creative classes for women with symptoms of PND.